A randomized, phase 2 evaluation of the CHK1 inhibitor, LY2603618, administered in combination with pemetrexed and cisplatin in patients with advanced nonsquamous non‐small cell lung cancer. (June 2017) - Wehler, Thomas; Thomas, Michael; Schumann, Christian; Bosch-Barrera, Joaquim; Viñolas Segarra, Nuria; Dickgreber, Nicolas J.; Dalhoff, Klaus; Sebastian, Martin; Corral Jaime, Jesus; Alonso, Miriam; Hynes, Scott M.; Lin, Ji; et al.
Highlights: LY2603618 (LY) is a selective checkpoint kinase 1 inhibitor. LY was added to standard first-line treatment for patients with nonsquamous NSCLC. Primary endpoint of significantly improved PFS was met with addition of LY. No statistically significant improvement in secondary efficacy endpoints with LY. There was a numerical increase in the rate of thromboembolic events with LY. Abstract: This phase 2 portion of a phase 1/2 study examined the efficacy and safety of LY2603618, a selective checkpoint kinase 1 inhibitor, combined with pemetrexed and cisplatin (LY + Pem + Cis) in patients with advanced nonsquamous non-small cell lung cancer (NSCLC). This multicenter, randomized, controlled, open-label study (NCT01139775) enrolled patients with stage IV nonsquamous NSCLC and an Eastern Cooperative Oncology Group performance status ≤1. Patients were randomized (2:1) to LY + Pem + Cis or pemetrexed and cisplatin (Pem + Cis). Induction therapy comprised four 21-day cycles of 500 mg/m 2 pemetrexed and 75 mg/m 2 cisplatin on Day 1 (both arms) and 275 mg LY2603618 on Day 2 (LY + Pem + Cis arm). Maintenance therapy comprised 500 mg/m 2 pemetrexed on Day 1 (both arms) and 275 mg LY2603618 on Day 2 (LY + Pem + Cis arm) until disease progression. The primary endpoint was progression‐free survival (PFS). Enrollment was permanently halted before target enrollment was met due to a greater number of thromboembolic events in the LY + Pem + Cis arm. Sixty-two patients were enrolled (LY + Pem + Cis, n = 39; Pem + Cis, n = 23). Bayesian and frequentist analysis demonstrated superior PFS in the LY + Pem + Cis arm vs the Pem + Cis arm (median [90% confidence interval]: LY + Pem + Cis, 4.7 months [4.–7.1]; Pem + Cis, 1.5 months [1.3–2.9]; P = 0.022). Seven patients in the LY + Pem + Cis arm (vs 0 in the Pem + Cis arm) experienced serious thromboembolic events: pulmonary embolism (n = 5), ischemic stroke (n = 1), and cerebrovascular accident (n = 1). Although the primary endpoint was met, the combination of LY2603618 + Pem + Cis will not be further developed for treating advanced nonsquamous NSCLC due to the potential increased risk of thromboembolic events with this combination. ClinicalTrials.gov Identifier: NCT01139775 .